Financial Literacy-based HRM: Optimizing Human Resource Performance Through Financial Education - Rostini; Nurmiati, Nurmiati; Siti Mariam; Yana Ameliana (Atestasi : Jurnal Ilmiah Akuntansi, 2023)
The purpose of this study is to analyze the causality of the relationship between Financial Education, Availability of Human Resources for Financial Education, Financial Knowledge, Adoption of Financial Behavior, HR Performance, Employee Financial Productivity, Corporate Financial Welbeing. This study uses a quantitative approach which is then processed using smartpls as an analysis tool. The data collection method used an online questionnaire addressed to 268 respondents. The results of this study state that overall, this research illuminates the importance of individual financial behavior in an organizational context. By highlighting Adoption of Financial Behavior as the focal point, this study shows that individual financial behavior has a significant impact on the company's financial well-being, employee productivity, and overall human resource performance. Managerial implications affirm the need for greater investment in financial education in the workplace to shape positive financial behaviors and support the financial well-being of the firm. Meanwhile, the theoretical implications reinforce the conceptual basis of the role of financial education in shaping prudent financial behavior in an organizational context. With an emphasis on financial education and a better understanding of individual financial behaviors, management can strengthen the financial foundation of the firm, increase employee productivity, and improve overall human resource performance, forming a crucial step towards sustainable financial well-being for the organization.